725 Serious Illness, Sleep Quality, and Spirituality: an exploratory study in a multicultural inpatient setting. (3rd May 2021) - Castro, Laura; Peteet, John; Balboni, Tracy; Koenig, Harold; Cintra, Fatima
Abstract: Introduction: Spiritual well-being can impact quality of life and survival among diseased populations, similarly to sleep. Despite beneficial effects of spiritual-based practices on sleep, few studies have investigated an association between these attributes. Our goal was to explore correlations between measures of sleep quality and spirituality among severe medical inpatients hospitalized for different reasons, testing whether sleep could be a mechanism by which spirituality influences clinical outcomes. Methods: Patients (18+ years) admitted in two units of the University's hospital between Oct/2018 and Aug/2019 were invited to participate. Semi-structured interviews included the Duke Religiousness Index, the Belief into Action Scale, the Functional Assessment of Chronic Illness Therapy Spiritual Well-Being, the Pittsburgh Sleep Quality Index (PSQI), and the Short Form Six-Dimension (SF-6D) health index. Diagnoses were defined by the International Classification of Diseases. We used the Chi-square test, bivariate correlations, and Generalized Linear Models. Results: A total of 146 consecutive patients were included (46.8±15.9 years, 51% men), 28% admitted for cardiovascular diseases, 26% for cancer, 20% rheumatologic disorders, and 26% for other conditions including hematological, nephro-urological, infectious, among other diseases. The mean PSQI was 10.1±4.7 and 55% of patients rated their sleep as poor. Average sleep duration was 6.5±1.9 hours. Insomnia (64%) was the most frequent sleep complaint, followed by nocturia (43%), pain (42%), and discomfort breathing (29%). There was a modest correlation between sleep quality and spiritual well-being (-0.23; p<0.01). Maintenance insomnia correlated with less spiritual peace/meaning (-0.27; p<0.01) and faith (-0.21; p=0.01), whereas pain, with more social (0.21; p=0.01) and private (0.24; p<0.01) religious activities. Initial insomnia also correlated with private activities (0.18; p=0.04). Seep quality (0.43; 0.25–0.62), spiritual peace/meaning (-0.21; -0.40-[-0.01]), and social religious activities (0.18; 0.04–0.32) were independent indicators of higher SF-6D scores, additional to an interacting effect between sleep quality and spiritual well-being predicting better quality of life. Conclusion: Subjective sleep quality is associated with spiritual well-being and quality of life, independently of the nature and severity of the medical disease. Our findings also suggest that patients suffering from nocturnal pain and trouble falling asleep might be more engaged with religious activities. Support (if any): Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)